A study on anxiety disorder among college students with internet addiction - Kandasamy, Sunitha; Buhari, Abdulrahuman Mohamed; Janaki, Shyamala (International Journal Of Community Medicine And Public Health, 2019)
Background: The last decade has seen a tremendous growth in internet usage with 3,486,642,862 present users worldwide with India contributing 462,124,989 users. Out of this 70% are young. In this scenario there is also drastic increase in the prevalence of psychiatric illness among the same vulnerable group. A lot of studies have been conducted to bring out the association of the psychiatric disorders with internet addiction. This study aims to estimate the prevalence of internet addiction among college students and bring to light the degree of association of anxiety disorder with internet addiction. Methods: A cross sectional study is carried out in 2 arts colleges in Tirunelveli city among 200 students (aged 19-21 years) using internet addiction test by Dr. Kimberly young and anxiety rating by Hamilton anxiety scale. Results: Among the 200 students, only 22% did not have internet addiction. 52% are average on-line users, 20% are possible addicts and 6% are addicts. Among these 59.6% had mild anxiety, 22.4% moderate anxiety and 17.9% suffered severe anxiety. 56.4% had anxious mood and fear and 38.5% suffer intellectual deterioration, 30.8% had depressed mood. 33.3% had experienced muscular somatic symptoms, 23% autonomic, 14.1% gastrointestinal symptoms and 7.7% cardiovascular symptoms and 24% respiratory symptoms. Conclusions: Internet addiction is an emerging health issue among youth, if left unattended will compromise the mental and physical well being of the youth. It is also mandate that a holistic education program that is based on positive youth constructs is the need of the hour.